ATTORNEY'S REQUEST FOR GIVING AN EXPERT OPINION IN THE CRIMINAL PROCEDURE CODE OF THE REPUBLIC OF KAZAKHSTAN: CORRECTIONS PART 1 - I. Borchashvili; L. Paramonova (Теория и практика судебной экспертизы, 2015)
This article соntains the analysis of the norms of the Criminal Procedure Code of the Republic of Kazakhstan governing the appointment and the production of forensic examinations attorney's request. The authors o*ers alternative formulations of rules containing gaps and collisions.